Renal Abscess Caused by Crizotinib: A Rare Case Report - Wan, Zhaojun; Wang, Kai; Yin, Xiangfu; Guo, Xiangting; Cheng, Guoli; Pan, Jihong (Frontiers in Oncology, 2022)
Crizotinib is a tyrosine kinase inhibitor that has been found to be effective in the treatment of c-ros oncogene 1 positive non-small cell lung cancer. Although this targeted agent to treat cancer has been shown superiority than standard chemotherapy in some ways, some adverse effects of this drug can be happened, such as the development of renal abscess. Some associated renal damage may disappear with crizotinib withdrawal. Hence, we present a case of a 58 year old male with non-small cell lung cancer on crizotinib therapy who developed bilateral renal unnormal space occupying successively, which was difficult to identify by various imaging methods, even PET-CT was highly suspected the right renal masses as malignant. Finally, the right renal lesions were confirmed as renal abscess by postoperative pathology. And the left renal lesion was considered for renal cysts through the lesion disappearing after crizotinib withdrawal. There have been very few reports in this respect, especially proved by various methods, confirmed by postoperative pathology. It is important to recognize this drug-related complication in order to avoid incorrect diagnosis and inadequate therapy. And it is necessary to monitor the renal changes after taking crizotinib.